Knowledge economy the Indian challenge - Chandra, Ashoka; Khanijo, M. K.; Sage eBooks (New Dehli ; London : SAGE, 2009)
'Knowledge Economy' addresses the challenge of transforming the Indian economy into a knowledge economy. It looks at change management of the economy and highlights issues such as economic trends and critical activities contributing to the desired change.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Knowledge management -- India; Information resources management -- India; Intellectual capital -- Economic aspects -- India; Electronic books